2019
DOI: 10.3390/app9040624
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Optimization Method for Energy Scheduling of Multiple Microgrids

Abstract: This paper proposes a hierarchical optimization method for the energy scheduling of multiple microgrids (MMGs) in the distribution network of power grids. An energy market operator (EMO) is constructed to regulate energy storage systems (ESSs) and load demands in MMGs. The optimization process is divided into two stages. In the first stage, each MG optimizes the scheduling of its own ESS within a rolling horizon control framework based on a long-term forecast of the local photovoltaic (PV) output, the local lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…While [1][2][3] focus on a single microgrid, [4] proposes a hierarchical optimization method for the energy scheduling of multiple microgrids connected to the distribution grid with participation in the energy market. The optimization procedure is separated into two stages.…”
Section: Discussionmentioning
confidence: 99%
“…While [1][2][3] focus on a single microgrid, [4] proposes a hierarchical optimization method for the energy scheduling of multiple microgrids connected to the distribution grid with participation in the energy market. The optimization procedure is separated into two stages.…”
Section: Discussionmentioning
confidence: 99%
“…Author of study observed that current MG applications are not able to manage the uncertainty and variability of energy resources, diversity of RES and suggested advanced stochastic algorithm, predictive analytics and no linear schemes for future MGs Due to the penetration of RES and the increasing number of DER data compatibility and exchange are emerging as major challenges for implementation of dynamic MG capabilities. Rui et al [116] proposed the two stage optimization method to address the uncertainties of RES and load. Energy market operator (EMO) is the upper level manager of multi MGs and MG operator (MGO) is the lower level manager of MGs in the proposed optimization model.…”
Section: Matlabmentioning
confidence: 99%
“…The autoregressive integrated moving average model was applied to obtain the predicted value of electrical loads and PV units. Rui et al [32] developed a mixed integer programming model and game model for optimal energy scheduling of multiple MGs. Mazzola et al [33] proposed a framework to determine the optimal energy scheduling of isolated rural MGs considering forecast-based dispatch in the MGs operation using a normalized root-mean-square error approach.…”
Section: Grid−tmentioning
confidence: 99%